Pengaruh Model Pembelajaran Problem Solving Terhadap Kemampuan Berpikir Kritis Siswa - Haryati Haryati (Mahesa Research Center, 2023)
This research aimed to measure the student’s critical Thinking Skills in Biology class. Quasi-Experiment was used in this research by using Pre test - Post test control group design. The sampling method was carried out by using random sampling model i.e., by voting. The sample obtained was XII IPA 3 as the first class which was taught by problem solving model. Then the second was XII IPA 2 class which was taught using conventional model . The instrument used in this research was multiple choice which is used to measure the student’s critical thinking skill. The normality test of problem solving model was 0,087, 0,058 was gained from the control class which means that these value are greater than 0,05, thus the data is normally distributed. The independent samples t-test showed that the value of significance is 0.020 0.05, so it can be concluded that the hypothesis Ha is accepted.